Electrocardiographic Parameters Indicating Worse Evolution in Patients with Acquired Long QT Syndrome and Torsades de Pointes. Issue 6 (28th March 2016) - Kukla, Piotr; Jastrzębski, Marek; Fijorek, Kamil; Stec, Sebastian; Bryniarski, Leszek; Czarnecka, Danuta; Baranchuk, Adrian
Abstract : Background: Acquired long QT syndrome (a‐LQTS) is associated with life‐threatening ventricular arrhythmias, mainly torsades de pointes (TdP). ECG parameters predicting evolving into ventricular fibrillation (VF) are ill defined. Aims: To determine ECG parameters preceding and during TdP associated with higher risk of developing VF. Methods: We analyzed 151 episodes of TdP, recorded in 28 patients with a‐LQTS (mean QTc 638 ms ± 57). Results: All 28 patients had prolonged QT interval, (mean QTc 638 ms ± 57) ranging from 502 ms to 858 ms correcting by Bazett's formula. The mean TdP heart rate was 218 bpm ± 38 (mean cycle length of TdP 274 ± 47 ms). We classified TdPs episodes into "slower"‐TdP (s‐TdP) < 220 bpm (range from 145–220 bpm) observed in 81 (53.6%) episodes and "faster"‐TdP (f‐TdP) ≥ 220 bpm (ranged from 221–281 bpm) observed in 70 (46.4%) episodes. Among 151 episodes of TdP, 21 (13.9%) were unstable (converted into VF). Out of 81 episodes of "slower"‐TdP only 2 (2.5%) episodes converted into VF. The mean coupling interval (CI) of the PVC initiating TdP was 510 ms ± 118, the pause‐RR interval was 1147 ms ± 335, the prematurity index (PI) of PVC that initiated TdP was 0.45 ± 0.13. The mean cycle length variability of TdP (VRV‐TdP) was 30.79 ms ± 19.7. U wave was observed in 86 episodes (56.9%), among that in 69 episodes, the U/T wave ratio was > 1. Macro T wave alternans was observed in 4 patients. The QT interval was not different in patients with VF(+) and VF(−) episodes, 633 ± 60 and 639 ± 57, respectively. Conclusions: Some electrocardiographic parameters can be helpful in determining the risk of TdP evolving into VF. The slower ventricular rate (< 220 bpm), the higher rate instability (VRV > 30 ms) and the short episodes < 20 beats could predict benign evolution.